Estrategias de comunicación organizacional para la difusión de la información en el Gobierno Autónomo Descentralizado Municipal del cantón Cumandà Provincia Chimborazo, año 2019 - Gavilanes Bustos, Angel David (2019)
The present research project presents the topic of “Organizational Communication Strategies for the dissemination of information in the Gobierno Atónomo Descentralizado Municipal Cumandá (city of Chimborazo Province), at the year 2019, with the design of a strategic organizational communication plan as a corrective measure to provide solutions to the communication problems that are arising in the institution. The methodology used for the preparation of this research is qualitative, based on this project, surveys were carried out on the internal public of the institution and to the external public of the Cumandá city. With the results obtained, the respective graphics were designed with analyzes and interpretations that were taken into consideration for the development of appropriate strategies. In addition, in general terms, the dissemination of information has to do with the design of the strategies that are being implemented within the municipality to achieve the adequate structure of the message, thus achieving the interaction between the institution and the community. It should be noted that in order to achieve this change in organizational communication and in the dissemination of information, all the information that has been provided by those responsible for the area currently working is taken into account, which has been very important. Keywords: Organizational Communication, Dissemination of information, Decentralized Autonomous Governments.